High monocytic MDSC signature predicts multi-drug resistance and cancer relapse in non-Hodgkin lymphoma patients treated with R-CHOP - Dhar, Sukanya; Chakravarti, Mohona; Ganguly, Nilanjan; Saha, Akata; Dasgupta, Shayani; Bera, Saurav; Sarkar, Anirban; Roy, Kamalika; Das, Juhina; Bhuniya, Avishek; Ghosh, Sarbari; Sarkar, Madhurima; et al. (Frontiers in Immunology, 2024)
Introduction: Non-Hodgkin Lymphoma (NHL) is a heterogeneous lymphoproliferative malignancy with B cell origin. Combinatorial treatment of rituximab, cyclophsphamide, hydroxydaunorubicin, oncovin, prednisone (R-CHOP) is the standard treatment regimen for NHL, yielding a complete remission (CR) rate of 40-50%. Unfortunately, considerable patients undergo relapse after CR or initial treatment, resulting in poor clinical implications. Patient’s response to chemotherapy varies widely from static disease to cancer recurrence and later is primarily associated with the development of multi-drug resistance (MDR). The immunosuppressive cells within the tumor microenvironment (TME) have become a crucial target for improving the therapy efficacy. However, a better understanding of their involvement is needed for distinctive response of NHL patients after receiving chemotherapy to design more effective front-line treatment algorithms based on reliable predictive biomarkers. Methods: Peripheral blood from 61 CD20+ NHL patients before and after chemotherapy was utilized for immunophenotyping by flow-cytometry at different phases of treatment. In-vivo and in-vitro doxorubicin (Dox) resistance models were developed with murine Dalton’s lymphoma and Jurkat /Raji cell-lines respectively and impact of responsible immune cells on generation of drug resistance was studied by RT-PCR, flow-cytometry and colorimetric assays. Gene silencing, ChIP and western blot were performed to explore the involved signaling pathways. Results: We observed a strong positive correlation between elevated level of CD33+CD11b+CD14+CD15- monocytic MDSCs (M-MDSC) and MDR in NHL relapse cohorts. We executed the role of M-MDSCs in fostering drug resistance phenomenon in doxorubicin-resistant cancer cells in both in-vitro, in-vivo models. Moreover, in-vitro supplementation of MDSCs in murine and human lymphoma culture augments early expression of MDR phenotypes than culture without MDSCs, correlated well with in-vitro drug efflux and tumor progression. We found that MDSC secreted cytokines IL-6, IL-10, IL-1β are the dominant factors elevating MDR expression in cancer cells, neutralization of MDSC secreted IL-6, IL-10, IL-1β reversed the MDR trait. Moreover, we identified MDSC secreted IL-6/IL-10/IL-1β induced STAT1/STAT3/NF-κβ signaling axis as a targeted cascade to promote early drug resistance in cancer cells. Conclusion: Our data suggests that screening patients for high titre of M-MDSCs might be considered as a new potential biomarker and treatment modality in overcoming chemo-resistance in NHL patients.